Prioritizing Athlete Health and Well-Being: Addressing Gaps in Coach Education and Practice for Relative Energy Deficiency in Sport, Nutrition, and Body Composition - Jessica Brooke Kirby; Maria Luisa F. Pereira Vargas; Lindsay Macnaughton; Sara Drummond; Luke Rodriguez; Nanna Meyer (International Sport Coaching Journal, 2025)
Coaches have substantial influence over athletes and a lack of education on the risk factors for Relative Energy Deficiency in Sport (REDs) which pose a significant risk to athlete health and well-being. The aim of this study was to explore coach education curriculum related to REDs, body composition, and nutrition to identify gaps which could be addressed to reduce risk of REDs. Interviews were conducted with 14 international national sport governing body representatives. Resulting themes included: challenges with coach education content and standards; policy development; evolving norms, attitudes, and practices; and the role of leveraging interdisciplinary expertise to support coach education and coaching practice. Findings revealed that most participants viewed REDs and body composition as important but few national sport governing bodies invested in sufficient education on these topics, and significantly no national sport governing bodies had explicit policies to protect athletes from REDs risk factors. An urgent call for improved REDs education, prioritized funding for athlete well-being, and progressive interprofessional collaboration is presented.